Evaluasi Efisiensi Boiler Pulverized Coal pada Co-Firing Sawdust PLTU Pacitan - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Muhammad Sayid Romdhoni (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates boiler efficiency in a pulverized-coal steam power plant during direct co-firing of sawdust biomass at PLTU Pacitan Unit 1. The analysis uses operational and performance-test data for coal firing and co-firing schemes with 1%, 2%, and 5% sawdust at approximately 295 MW load. Boiler efficiency was calculated using the indirect heat-loss method based on ASME PTC 4, supported by fuel ultimate and proximate analysis, heat-loss components, fuel rate, air-heater gas temperature, and emission measurements. The results show that increasing sawdust composition changes fuel characteristics, especially lower gross calorific value, lower sulfur and ash content, higher total moisture, and lower Hardgrove Grindability Index. Boiler efficiency on an LHV basis reached 91.96% for 100% coal, 92.61% for 1% sawdust, 92.30% for 2% sawdust, and 91.74% for 5% sawdust. At 5% co-firing, fuel consumption increased by about 1.19% compared with coal firing, while SO2, NOx, and particulate emissions decreased and remained below the regulatory limits. The study indicates that sawdust co-firing can support emission reduction, but boiler efficiency and fuel handling require continuous monitoring